Stratigraphic Determination Based on Shear Wave Velocity for Earthquake Disaster Mitigation in Lebong District - Jaya, Shara Ashari Prana Jaya; Refrizon, Refrizon; Halauddin, Halauddin; Al Ansory, Andre Rahmat; Abimayu, Dadin Mars; Sholeha, Della Zakia; Apriana, Yelda (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
Bengkulu Province, including North Bengkulu and Lebong, is located in the subduction zone of the Indo-Australian and Eurasian plates, which makes the region prone to earthquakes. This research focuses on earthquake disaster mitigation in the Lemeu area, Uram Jaya District, and Lebong Regency. It identifies areas prone to earthquake shaking based on Vs stratigraphy, Vs30 distribution, and soil site class. The Vs value was measured directly using the Multichannel Analysis of Surface Wave (MASW) method for three passes. Each track has four stations, so there are 12 data collection stations. The station point is the center point of a series of 24 geophones. Each geophone has a recording time of 512 ms and a sampling rate time of 125 ms to obtain 4096 data for each geophone. The measurement data was processed using WINMASW 5.0 professional software to produce a 1D profile. From the stratigraphic Vs, Vs30 is calculated and used to determine the site class, and then a distribution map is made. The results show that this area consists of site classes D, C and B. Medium soil with a value range of 175 ≤ Vs30 ≤ 350, hard soil with a value range of 350 ≤ Vs30 ≤ 750 and soft rock with a value range of 750 ≤ Vs30 ≤ 1500. Of the 12 measurement points, 2 locations have relatively shallow Vs30 values, namely at points 4 and 11. This location has Vs30 values ranging from 221 - 258 m/s, so around this point, there is likely a high potential for building damage in the event of an earthquake.